Pembelajaran Berbasis Kognitif Multimedia pada Kalbu Perspektif al-Qur’an - idrus, idrus; Isyanto, Nur (Al Ashriyyah, 2023)
This study explores the application of multimedia cognitive theory in learning to understand its effect on learners' emotions and mental feelings. The focus of this study is on classroom conditioning and the use of multimedia elements such as images, sounds, music, animation, and text on the screen, along with the instructor's expressions. The purpose of the study is to increase the effectiveness and motivation of learners and make learning more interesting and meaningful. This research uses a qualitative approach with literature research methods. Primary data sources come from Qur'anic exegesis, while secondary data sources involve books, journals, and related research. Data analysis is carried out through content analysis methods, focusing on identifying key patterns and concepts. By combining both data sources, this study forms a strong basis for understanding the impact of multimedia cognitive theory on learners' emotions and motivation in the context of learning. Research findings indicate that the use of images and sounds as stimuli through two sensory channels, eyes and ears, can evoke emotions in the hearts of learners. The study also draws on concepts in the Qur'an, reinforcing the idea that eyes and ears have an important role in influencing human understanding and feeling. The conclusion of this study confirms that the application of multimedia cognitive theory in learning can increase the effectiveness and motivation of learners. By referring to these findings and ethnographic analysis approaches, this study provides new insights into the potential of multimedia in creating more engaging and meaningful learning experiences.